Um conto sobre representa??es de professores e estudantes acerca da rela??o educativa e da motiva??o para aprendizagem - Santana, Claudson Cerqueira (2020)
Brazilian Higher Education has been going through a process of change, starting from the transition that occurs in the national and international political-economic scenario, which directly affects teaching, which is no longer seen as the space for critical intellectual production and forming of opinions, passing in many cases, be based on the fast transmission of information and manpower training for the market. Of course, such a context, together with the entry of students from other cultures who were outside the academic space, as well as new teachers, called to take teaching in recent years there has been an expansion of enrollment and interiorization of universities, many of which no a pedagogical and didactic training, has reverberated in the relations between teachers and students in the classroom and, consequently, in motivating students in their learning process. From, we developed the following research problem: As the educational relationship between teachers and students implies the motivation for learning of college students? This argumentative paper presents the general objective of understanding the implications of the educational relationship in the motivation for learning of students of Exact Area of the degree courses of the State University of Feira de Santana (UEFS). (Degree in Mathematics, Physics and Chemistry). The investigation of qualitative character, was carried out as required to complete the Master of Education Program of Graduate Studies in Education of UEFS. The research was data production tool a socialprofessiographic questionnaire and a narrative interview with the participation of twelve employees, and six teachers and six students of the Degree courses in Physics, Mathematics and Chemistry. Data were analyzed from some assumptions of content analysis developed by Bardin (1977). The theoretical basis of this study was based on the Theory of Social Representations of Serge Moscovici (1978; 2007), in the conceptions of educational relationship, developed by Marcel Postic (2007), in addition to other studies on university classes (ARAUJO, 2008; VEIGA, 2008; DUSSEL & CARUSO, 2003 ANASTASIOU, 2004) and motivation for learning (FITA; 2003; BZUNECK, 2001). The main results of the research show that, first, student profiles that enter in the classroom during the day and at night are well differentiated. Serge Moscovici (1978; 2007), in the conceptions of educational relationship, developed by Marcel Postic (2007), and others on studies of university class (Araujo, 2008; VEIGA, 2008; Dussel & CARUSO, 2003 ANASTASIOU, 2004) and motivation for learning (FITA; 2003; Bzuneck, 2001). The main results of the research show that, first, student profiles that enter in the classroom during the day and at night are well differentiated. Serge Moscovici (1978; 2007), in the conceptions of educational relationship, developed by Marcel Postic (2007), and others on studies of university class (Araujo, 2008; VEIGA, 2008; Dussel & CARUSO, 2003 ANASTASIOU, 2004) and motivation for learning (FITA; 2003; Bzuneck, 2001). The main results of the research show that, first, student profiles that enter in the classroom during the day and at night are well differentiated. Second, that the representations brought show a diversity of profiles of university professors, many of which are not concerned with the student's learning process, even though they have committed to the content required by the curriculum component, while others seek to approach academics, seeking to know them, decorate their names and carry a friendship that can contribute to the climate of the classroom in favor makes learning. Third, the research showed that institutional characteristics influence the relationship between teachers and students in the classroom, reverberating in teaching practices and student motivation to learn. Fourth, were immersed different representations of motivation for learning in the narrative of the subjects, and the relationship students have with teachers influences their motivation in the classroom.